Seasonal Indicators of Blood Pressure, Data of Asthma Control Questionnaires and Quality of Life in Hypertensive Patients with Bronchial Asthma - G. F. Andreeva; M. I. Smirnova; V. M. Gorbunov; A. S. Kurekhyan; Ya. N. Koshelyaevskaya (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To study the seasonal indicators of quality of life and control of bronchial asthma in hypertensive patients with bronchial asthma, observed by a cardiologist of the state outpatient institution.Material and methods. Data from a prospective cohort study of hypertensive patients, some of which had bronchial asthma without exacerbation, were analyzed. Patients who were observed by a cardiologist at a state outpatient clinic took part in the study. There were other concomitant diseases that occurred in the participants, in addition to hypertension and bronchial asthma. Two groups of patients were formed: the control group (n=85) included patients with hypertension only, the main group (n=40) included hypertension and bronchial asthma. Patients had 3 visits: initial one, and after 6 and 12 months and then data on outcomes (30.1Ѓ}7.6 months of follow-up) were collected. The first and third visits included clinical measurements of blood pressure (BP), 24-hour BP monitoring, spirometry, clinical and biochemical blood tests, a standard survey, survey with questionnaires evaluating the control of bronchial asthma (Asthma Control Questionnaire; ACQ) and the patients quality of life (General Well-Being Questionnaire; GWBQ). The second visit included clinical BP and ACQ and GWBQ questionnaires. A comparison of the average indicators from the total number of observations carried out in winter, spring, summer and autumn periods has been performed.Results. Hypertensive patients with/without bronchial asthma (n=125; 28 men, 97 women, average age 62.6Ѓ}8.8 years, duration of hypertension – 11.6Ѓ}8.6, duration of bronchial asthma – 9.3Ѓ}11.9 years) took part in the study. Outpatient BP levels throughout the study period were maintained at target values in both groups. It was shown that seasonal BP levels do not differ in the compared groups, except for winter indicators: winter daytime systolic BP levels were higher in the main group (p=0.03). Seasonal fluctuations in BP were not detected in the control group, however, they were present in the patients of the main group: winter daytime levels of diastolic BP and average daily levels of diastolic BP and systolic BP were higher than summer ones, and winter daytime systolic BP values (p<0.05) and clinical diastolic BP (p=0.004) – higher than autumn levels. Seasonal quality of life indicators in the main group were worse than in the control group in all seasons. Significant seasonal dynamics of quality of life indicators in patients in two groups was not detected. The ACQ questionnaire showed that asthma control changed in different seasons in accordance with the ACQ total score: in winter and spring – uncontrolled bronchial asthma (total score >1.5), in summer and autumn – partially controlled (total score ≤1.5). During the analysis of various factors associated with the combined primary endpoint (death, transient ischemic attack, angina pectoris, cardiac arrhythmias, arterial revascularization), relationships with quality of life indicators were revealed: negative connections – with indicators characterizing positive psychological health, mood at visit, positive correlations – with psychological abilities.Conclusion: Seasonal fluctuations in ambulatory BP levels were not found in the control group and were found in the main group. The quality of life indicators for patients of the main group were significantly worse than in the control group for all components in all seasons. The control of asthma changed in different seasons in accordance with the ACQ total score: uncontrolled bronchial asthma occurred in winter and spring, partially controlled – in summer and autumn. Correlations of the combined primary endpoint with quality of life indicators were found after analyzing various factors.